A study of the Interaction Between Cetirizine and Plasma Membrane of Eosinophils, Neutrophils, Platelets and Lymphocytes using A fluorescence Technique - A. Kantar; N. Oggiano; P. L. Giorgi; J-P. Rihoux (Hindawi Limited, 1994)
The effect of cetirizine on plasma membrane fluidity and heterogeneity of human eosinophils, neutrophils, platelets and lymphocytes was investigated using a fluorescence technique. Membrane fluidity and heterogeneity were studied by measuring the steady-state fluorescence anisotropy and fluorescence decay of 1-(4- trimethylammonium-phenyl)-6-phenyl-1, 3, 5-hexatriene (TMA-DPH) incorporated in the membrane. The results demonstrate that cetirizine (1 μg/ml) induced a significant increase in the Hpid order in the exterior part of the membrane and a decrease in membrane heterogeneity in eosinophils, neutrophils and platelets. Moreover, cetirizine blocked the PAF induced changes in membrane fluidity in these cells. Cetirizine did not influence significantly the plasma membrane of lymphocytes. These data may partially explain the effect ofcetirizine on inflammatory cell activities.